Illegal Conduct After the Decision of the Constitutional Court Number 03/Puu-Iv/2006 On Corruption Crime - I Gusti Ngurah Agung Permata Dewa; Zuhro Nurindahwati; Kadek Dedy Suryana (International Journal Labs, 2024)
One of the phenomenal formulations of the Article is